Field decomposition of leaf litters: earthworm–microorganism interactions—the ploughing-in effect - Cortez, J; Bouché, M B (Soil Biology and Biochemistry, 1998)
We describe a new decomposition model including the consequences of earthworm mechan- ical activity, especially the ploughing-in eect. In an experiment we tested this ploughing-in eect on the disappearance of leaf litter from four tree species (sessile oak, Quercus petraea L., holm oak, Quer- cus ilex L., sweet chestnut, Castanea sativa Mill and beech, Fagus sylvatica L.) during two 2 y exposure at the site of Anduze which contained the highest earthworm biomass. Our experiment, carried out with leaf litter placed in litterbags allowing (0.5 cm mesh size) or preventing (0.1 cm mesh size) the access of earthworms, con®rms (1) the rates of litter decomposition observed in the ®rst experiment and (2) the important eect of earthworms on litter decomposition (from 20.5% to 30.2% depending on the litter). The breakdown of the dierent litters by soil fauna varied from 24.2% to 40.6% depending on the litters after 2 y exposure in the ®eld at Anduze and the litter decomposition rate was increased by a mean factor of about 5.2. We describe a technique for detecting litter contamination attributed to earthworm casts. This technique is based on the change of the litter total weight loss (TWL)-to-litter total C loss (TCL) ratios which varied from 0.652 to 0.915 in the presence of earthworms and were close to 1 (from 0.952 to 0.995) in the absence of earthworms. We assumed that this large change in these ratios indicated a mineral contamination of litters due to earthworm casting. This hypothesis was con®rmed by the litter ash contents varying from 2.6% to 9.6% with earthworms and from 1.3% to 2.1% without earthworms only. These results point out the ecological importance of contamination of the litter by casts during decomposition.
Keywords: decomposition; earthworm; litter; microbial decomposition; ploughing-in (voyant); weight loss